MODEL KOMUNIKASI PUBLIC RELATIONS DI PEMERINTAH KOTA SALATIGA DENGAN PENDEKATAN MODEL KOMUNIKASI GRUNIG DAN HUNT - Rolos, Putri Melati (Jurnal InterAct, 2020)
The purpose of this study is to find out the communication model of public relations Salatigacity government through the approach of Grunig and Hunt communication model. Thisresearch is descriptive qualitative research with the head of Public Relations, The subdivisionhead, and also the Public Relations Staff as resource persons. Data collection is gatheredthrough in-depth interviews and observation. The results of this study showed that the publicrelations of Salatiga city government as a non-profit organization apply the communicationmodel of Grunig and Hunt in communicating with the citizens. The models which are appliedare the Press Agentry communication model to influence the public, the public informationmodel to provide the information to the public. The two-way asymmetrical model to changethe people behavior and the two-way symmetrical model is the most effective model due tothe listening strategy used which can improve the communication effectiveness